Analysis Of The Influence Of Product Quality, Price Perception, Promotion, And Location On The Purchasing Decisions Of Civiartss Bouquets Among Students In Surabaya - Uci Silvia Rahmah; Ugy Soebiantoro (Journal of Economic, Bussines and Accounting (COSTING), 2024)
A bouquet business is a promising and timeless venture. Various types of products are offered with a wide range of creative designs. The business is supported by the trend of celebration events, particularly thesis defense celebrations by university students, which have made bouquets highly sought after, with orders often reflecting the latest trends. This study aims to determine the influence of product quality, price perception, promotion, and location on students' purchasing decisions for Civiartss bouquets in Surabaya. The research employs a quantitative method involving 100 respondents selected through purposive sampling. The respondents consist of university students in Surabaya who have purchased Civiartss bouquets and are enthusiasts of celebrations. Data collection involved both primary and secondary data, and the analysis was conducted using the Partial Least Squares (PLS) technique with validity, reliability, and hypothesis testing. The results of the study indicate that (1) there is a significant and positive influence of product quality on the purchasing decisions for Civiartss bouquets, (2) there is a significant and positive influence of price perception on the purchasing decisions for Civiartss bouquets, (3) there is a significant and positive influence of promotion on the purchasing decisions for Civiartss bouquets, and (4) there is a significant and positive influence of location on the purchasing decisions for Civiartss bouquets.